2017
DOI: 10.1515/anre-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and health status of children and adolescents in medieval Central Europe

Abstract: Subadult growth and health have been analyzed in three cemetery samples from medieval Poland, including two early-urban sites: Cedynia dated to the 10th-14th centuries AD, and Ostrów Lednicki dated to the 13th-15th centuries AD, and a rural site Słaboszewo dated to the 14th-17th centuries AD. The nutritional status was not expected to have substantially differed among the settlements, due to the culturally induced undiversified diet of children, and predominant share of medium-to-low status individuals. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…The very low frequency of occurrence of Harris lines shows an absence of pathological and nutritional stress in this group (Piontek, Jerszyńska & Nowak, 2001). The prevalence of enamel hypoplasia in individuals from Cedynia fluctuates around 20% (Krenz-Niedbała, 2017), indicating the rare occurrence of physiological stress episodes during childhood. Compared to other European medieval populations, the analyzed group shows a low level of experience of stress events and nonspecific infections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The very low frequency of occurrence of Harris lines shows an absence of pathological and nutritional stress in this group (Piontek, Jerszyńska & Nowak, 2001). The prevalence of enamel hypoplasia in individuals from Cedynia fluctuates around 20% (Krenz-Niedbała, 2017), indicating the rare occurrence of physiological stress episodes during childhood. Compared to other European medieval populations, the analyzed group shows a low level of experience of stress events and nonspecific infections.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other European medieval populations, the analyzed group shows a low level of experience of stress events and nonspecific infections. Moreover, the medieval individuals constitute a homogenous group in terms of ethnicity and religion (Krenz-Niedbała, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The material used in this study came from an early medieval cemetery in Ostrów Lednicki (Poland) (mid‐11th to the end of the 12th century) (Ćwirko‐Godycki, ), an early urban site (stronghold) which played an important social and political role, as it was one of several residences of the Polish kings of that time (Krenz‐Niedbała, ). It was a skeletal burial cemetery.…”
Section: Methodsmentioning
confidence: 99%
“…The disruption of chondrocytes proliferation or differentiation (presented on the right side) makes the growth plate impenetrable for osteoblasts, which in turn begin to create a mineralized layer along the horizontal layer of chondrocytes at the end of the epiphyseal plate; they form a primary stratum perpendicular to the long axis of the medullary cavity. Prolonged periods of growth arrest result in the thickening of the primary stratum, which leads to the deposition of a Harris line (Scott and Hoppa 2015) populations found in numerous studies (Piontek et al 2001;Beom et al 2014;Geber 2014;Zapala et al 2016;Krenz-Niedbała 2017). In addition, even if it will be concluded that HLs are poorly suited for determining the health of individuals (as it may be a result of non-pathological processes), they can still be useful for determining the overall health at the population level (Nowak and Piontek 2002b): assuming that the occurrence of HL unassociated with any pathologies is (more or less) constant, statistically different frequency of HL between the compared populations would result from different occurrence of HL associated with pathologies or physiological stress.…”
Section: Introductionmentioning
confidence: 97%
“…There was no statistically significant correlation between bone length and morphology and the occurrence of HL (Mays 1985;Nowak and Piontek 2002b). Moreover, numerous researchers have failed to find correlations between the age of enamel hypoplasia (EH) and HL formation, suggesting that HLs are a physiological rather than a pathological phenomenon (Piontek et al 2001;Beom et al 2014;Geber 2014;Zapala et al 2016;Krenz-Niedbała 2017). Due to the similarities between the somatotropin (growth hormone) secretion curves, the long bone growth curves, and the distribution of HLs, it was suggested that HLs are associated with physiological periods of faster and slower growth (Papageorgopoulou et al 2011).…”
Section: Introductionmentioning
confidence: 99%